MUHAMMADIYAH DAN INOVASI PENDIDIKAN ISLAM - Sri Suci Wahyuningsih (Universitas Islam Negeri Sumatera Utara Medan, 2019)
This research is intended to explore the implementation of education at IslamicInstitution of Muhammadiyah Schools. This research focus on what innovation thatthis Islamic organization applied in their schools. This research used library andfield method. The data were collected by using documentation study and deepinterview with educational staffs. The results of this research revealed that thisIslamic Organisation runs basic education until university. In every level ofeducation there is one subject called “Al Islam Kemuhammadiyahan” as typicalsubject of this organasation. The Schools still maintained their identity as IslamicOrganization but they also used modern education to fulfill the advance ofeducational, especially in higher education.